SoundScapeGenerator: soundscape modelling and simulation - Koutsomichalis, Marinos; Valle, Andrea (My University, 2014)
This paper describes SoundScapeGenerator, a generic sys- tem for modelling and simulating soundscapes both in real and non-real time. SoundsScapeGenerator features algorithms for three-dimensional sound-localisation and is able to model complex spaces. The system relies on abstract rule descriptions (generators) to simulate deterministic, “car- toonified” (loosely modelled) sequencing of sound events. It further supports virtual P.O.H. (point of hearing) and is able to render the final output in various channel con- figurations. Based on generative algorithms, the Sound- ScapeGenerator implementation allows real-time user interaction with ever-changing soundscapes, and it can easily communicate with other applications and devices. Finally, we introduce SoundScapeComposer, a higher level module developed for the SoDA project (dedicated to soundscape automatic generation), that has been built on top of SoundScapeGenerator, hiding most of the latter’s details to the user.
Keywords: SoundsScapeGenerator features; Point of hearing